Whole genome sequence of Vibrio cholerae NB-183 isolated from freshwater in Ontario, Canada harbors a unique gene repertoire - Opeyemi U. Lawal; Noah Bryan; Mitra Soni; Yanhong Chen; Melinda Precious; Valeria R. Parreira; Lawrence Goodridge (BMC Genomic Data, 2024)
Abstract Objective Vibrio cholerae is an enteric pathogen that poses a significant threat to global health. It causes severe dehydrating diarrheal disease cholera in humans. V. cholerae could be acquired either from consuming contaminated seafood or direct contact with polluted waters. As part of a larger program that assesses the microbial community profile in aquatic systems, V. cholerae strain NB-183 was isolated and characterized using a combination of culture- and whole-genome sequencing-based approaches. Data description Here we report the assembled and annotated whole-genome sequence of a V. cholerae strain NB-183 isolated from a recreational freshwater lake in Ontario, Canada. The genome was sequenced using short-read Illumina systems. The whole-genome sequencing yielded 4,112,549 bp genome size with 99 contigs with an average genome coverage of 96× and 47.42% G + C content. The whole genome-based comparison, phylogenomic and gene repertoire indicates that this strain harbors multiple virulence genes and biosynthetic gene clusters. This genome sequence and its associated datasets provided in this study will be an indispensable resource to enhance the understanding of the functional, ecological, and evolutionary dynamics of V. cholerae.